Influência da Ovariectomia e da reposição hormonal com estradiol no reparo ósseo alveolar pós-exodontia de ratas sob terapia com alendronato de sódio - Isaias, Pedro Henrique Chaves (2024)
Prolonged use of bisphosphonates in the treatment of osteoporosis, such as sodium alendronate (ALN), is associated with adverse effects, including jaw osteonecrosis, especially in patients undergoing tooth extractions. Estrogen deficiency, caused by menopause or ovariectomy (OVX), exacerbates bone loss, but hormone replacement with estradiol has been used to mitigate these effects. However, the impact of the interaction between postmenopausal osteoporosis, ALN, and hormone therapy on alveolar bone healing remains uncertain. Thus, this study aimed to evaluate the effect of OVX and ALN treatment, with or without estradiol valerate (E) hormone replacement, on alveolar bone repair after tooth extraction in rats. The study was conducted on 63 Wistar rats (180-220g), divided into nine experimental groups. The groups underwent either OVX surgery or sham surgery (SHAM). After eight weeks, they were treated with saline solution (SAL) or ALN (5.0 mg/kg or 10.0 mg/kg) via gavage twice weekly. Three additional groups also received hormone replacement with E (0.8 mg/kg/day) starting one week after OVX. On the 42nd day of bisphosphonate treatment, all groups underwent extraction of the left first lower molar. The animals were euthanized on day 70, and the extraction sites were subjected to clinical, radiographic, histological (H&E, Picrosirius Red), and immunohistochemical (TNF-α, RANKL, OPG, TRAP) analyses. Body mass, uterine wet mass, and femur morphology were also analyzed. OVX significantly increased body mass, reduced uterine wet mass, and increased the medullary area of the femoral head (partially reversed by ALN) compared to SHAM groups (p-Value OVX<0.001). Radiographically, the ALN-treated groups, especially at 10.0 mg/kg, showed a larger radiolucent area at the extraction sites (p-Value ALN=0.040). Histologically, ALN and OVX groups exhibited more fibrous connective tissue in the socket (p-Value OVX<0.001; ALN=0.0002), an increase in empty osteocyte lacunae (p-Value OVX=0.001; ALN<0.001), and vacuolated osteoclasts (p-Value OVX<0.001; ALN=0.0063). Hormone replacement with E mitigated these effects. The ALN5- SHAM groups showed greater deposition of total collagen and type I collagen compared to the ALN10-SHAM and ALN5-OVX+E groups. Type III collagen was more abundant in the OVX and ALN10-SHAM groups but was partially reduced by E replacement [total collagen (p-Value I=0.022; OVX<0.001; ALN=0.011), type I collagen (p-Value I=0.014; OVX<0.001; ALN=0.015), and type III collagen (p-Value I<0.001; OVX=0.002; ALN<0.001)]. Immunohistochemistry revealed that ALN-treated groups showed increased TNF-α levels (p-Value I=0.004; OVX=0.001; ALN<0.001), with a slight reduction after E replacement. The SAL-OVX group had more TRAP-positive osteoclasts, which were reduced in the SALOVX+ E group (p-Value I=0.030). RANKL levels increased in ALN-treated groups (p-Value I=0.002; OVX<0.001; ALN<0.001), but decreased with E. OPG levels were reduced in the ALN-SHAM, ALN-OVX, and ALN-OVX+E groups (p-Value I<0.001; ALN<0.001). The RANKL/OPG ratio increased with ALN but decreased after E replacement (p-Value I<0.001; OVX<0.001; ALN<0.001). ALN treatment delayed alveolar bone healing, exacerbated by OVX, which also increased TRAP-positive osteoclasts and caused systemic alterations. E replacement reduced these effects, improving healing and decreasing osteoclastic activity. ALN elevated TNF-α and the RANKL/OPG ratio, but these impacts were partially attenuated by E. These findings suggest that E replacement may protect against imbalanced bone resorption and minimize the adverse effects of ALN in estrogen-deficient patients.